The Disadvantages of Learning English through Facebook (مجلة العلوم الشاملة, 2025)
Learning a foreign language needs students to focus continuously while receiving organized language input and chances to practice meaningfully and feedback from trustworthy sources. Students now learn English through unofficial online learning platforms because digital technology has brought major changes to their English learning methods. Facebook serves as a well-known platform which English learners use to access thousands of pages and groups which offer grammar tips and vocabulary learning and short videos and peer interaction opportunities.The platform of Facebook attracts students because it provides both entertaining content and English learning materials at no cost through its simple access. Students who do not have access to traditional education can learn languages through social media platforms which serve as their educational resource. The educational worth of using Facebook as the primary learning platform has not been determined yet. The system provides motivational support and casual user interaction but its design structure and content organization create major problems for students who want to build precise language abilities that can be applied in different situations.The paper evaluates all the negative aspects which occur when students depend on Facebook for their English language education. The research from computer-assisted language learning (CALL) and informal digital learning of English (IDLE) and educational technology demonstrates that Facebook lacks structured learning because it presents unorganized language material with limited feedback possibilities and strong distractions which raise ethical issues that make it inappropriate for basic learning requirements. The discussion centers on students who need to develop academic or professional language abilities instead of learning for fundamental exposure or entertainment purposes.